PHLDA1, another PHLDA family protein that inhibits Akt. Issue 11 (13th October 2018) - Chen, Yu; Takikawa, Masahiro; Tsutsumi, Shuichi; Yamaguchi, Yoko; Okabe, Atsushi; Shimada, Mayuna; Kawase, Tatsuya; Sada, Akane; Ezawa, Issei; Takano, Yuhei; Nagata, Kisaburo; Suzuki, Yutaka; et al.
Abstract : The PHLDA family (pleckstrin homology‐like domain family) of genes consists of 3 members: PHLDA1, 2, and 3 . Both PHLDA3 and PHLDA2 are phosphatidylinositol (PIP) binding proteins and function as repressors of Akt. They have tumor suppressive functions, mainly through Akt inhibition. Several reports suggest that PHLDA1 also has a tumor suppressive function; however, the precise molecular functions of PHLDA1 remain to be elucidated. Through a comprehensive screen for p53 target genes, we identified PHLDA1 as a novel p53 target, and we show that PHLDA1 has the ability to repress Akt in a manner similar to that of PHLDA3 and PHLDA2. PHLDA1 has a so‐called split PH domain in which the PH domain is divided into an N‐terminal (β sheets 1‐3) and a C‐terminal (β sheets 4‐7 and an α‐helix) portions. We show that the PH domain of PHLDA1 is responsible for its localization to the plasma membrane and binding to phosphatidylinositol. We also show that the function of the PH domain is essential for Akt repression. In addition, PHLDA1 expression analysis suggests that PHLDA1 has a tumor suppressive function in breast and ovarian cancers. Abstract : Through a comprehensive screening for p53 target genes, we identified pleckstrin homology‐like domain family, member 1 (PHLDA1) as a novel p53 target, and we show that PHLDA1 has the ability to repress Akt in a manner similar to that of other PHLDA family proteins. We show that the PH domain of PHLDA1 is responsible for its localization to the plasma membrane, and PHLDA1 has the ability to bind to phosphatidylinositols and repress Akt. In addition, PHLDA1 expression analysis suggests that PHLDA1 has a tumor suppressive function in breast and ovarian cancers.